Metal organic framework (MOF) in aqueous energy devices - Tan, Hua (2022)
Aqueous energy devices are under the spotlight of current research due to their safety, low cost and ease of handling. Metal-organic frameworks (MOFs) and their derivatives have spurred extensive exploration as they provide a library of new electrode materials. The rich and structural flexibilities (such as metal nodes, ligands, pore structure) endow MOFs and MOFs-derivatives with vast opportunities for various energy devices. In this review, we discuss the correlation between MOF structural parameters and electrochemical performance for aqueous energy devices in the scope of zinc-based batteries (Zn-ion, Zn-alkaline and Zn-air batteries), potassium-ion batteries and supercapacitors. For each energy device, the effect of determinative factors and structural modulating strategies of MOFs and derivatives are highlighted. Finally, we summarize the challenges and provide our perspective about MOFs and derivatives for future aqueous energy devices.